Ojibwa discursive practices in the Eastern Upper Peninsula of Michigan - Jackson, Deborah Davis; Holappa, Ted (1996)
Recordings made in Hessel, Michigan from August to October of 1996, collected by Deborah Davis Jackson. Tapes 1-7 consists of elicitations of Ojibwe words and phrases. Tape 8 contains a life-historical interview with a brother and sister. Recording sessions were conducted by Ted Holappa, with consultant speakers who were given pseudonyms for the recordings.